Prevalence of Mycoplasma hominis and Ureaplasma urealyticum infection in female sex workers and its association with douching: A study in East Jakarta, Indonesia using Mycoplasma System Plus - Padang, Caroline; Jacoeb, Tjut Nurul Alam; Nilasari, Hanny; Daili, Sjaiful Fahmi (Journal of General - Procedural Dermatology and Venereology Indonesia, 2015)
Background: Mycoplasma hominis and Ureaplasma urealyticum are commonly involved in pathogenesis of bacterial vaginosis and non-specific genital infection, while doing vaginal douching also already known as predisposing factor. Methods: To evaluate the prevalence of Mycoplasma hominis and Ureaplasma urealyticum infection in female sex workers and its association with vaginal douching, we conducted a study through 180 female sex workers in East Jakarta, Indonesia. Vaginal fluid samples were collected from these women. It was revealed that most of the women used betel soap, baby soap, tooth paste, or herbal medicine as vaginal douching materials. The association of vaginal douching and prevalence of Mycoplasma hominis and Ureaplasma urealyticum was analyzed using cross sectional statistical methods. Results: There is a high prevalence of Mycoplasma hominis and Ureaplasma urealyticum infection (72%), but there are no association between vaginal douching practice and infection of Mycoplasma hominis and Ureaplasma urealyticum. Conclusions: The high prevalence of Mycoplasma hominis and Ureaplasma urealyticum infection in female sex workers in East Jakarta warrants a routine screening of these infections. Unusual1 materials used for vaginal douching in this study might cause the negative association between high prevalence of these bacteria with vaginal douching.